Advantages evaluation of integrating administrative and functional zones based on Island political location potential theory: A case study of the Zhoushan Archipelago New Area in China - Linhan Shao; Tingting Xu; Kaiyong Wang; Yufan Chen (PLoS ONE, 2025)
Administrative division adjustment is a new reform method and policy tool designed to align with local economic foundations and revitalize the development potential of administrative districts. However, it lacks systematic and quantifiable theories and methods. In response, we propose the Political Location Potential (PLP) model based on production functions, which is specifically applicable to islands. Using the Zhoushan Archipelago New Area as a case study, we analyze the efficiency and mechanisms behind the establishment of China’s first archipelago new area. The PLP model consists of two key components: horizontal production resource allocation capability and vertical administrative management authority. The PLP of Zhoushan City has increased from 0.007 in 2008 to 0.066 in 2022, with a relative potential energy of 2.853, 3.717 and 1.449 during the critical stages of 2010–2014, 2008–2013 and 2013–2018, respectively. Competitive comparative advantage and land-island connectivity capability have significant direct and indirect effects on the PLP of the island, but the impact effect shows a lag effect, with a lag period of 3–5 years. The theory and model of the PLP offer strong explanatory power for the effects of integrating administrative and functional zones, providing a fresh analytical perspective for local administrative division planning.